2000
DOI: 10.1017/s002202990000412x
|View full text |Cite
|
Sign up to set email alerts
|

Mammary infection with Staphylococcus aureus in cows: progress from inoculation to chronic infection and its detection

Abstract: S. The progress of Staphylococcus aureus infection from inoculation to the early chronic stage was examined in 12 Israeli-Holstein cows (four primiparous and eight multiparous) for up to 48 d after inoculation. Before inoculation, the primiparous cows were free from any infection and the multiparous cows were infected by coagulase-negative staphylococci. Two quarters in each cow were inoculated intracisternally following milking with 2000 cfu of a local prevailing Staph. aureus strain, VL-8407. Infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 33 publications
2
17
0
3
Order By: Relevance
“…This result was similar to the report of Rivas et al [27], who observed increases of CD4 cells in the mammary gland in an experimental study using cows with S. aureus infection. A significant increase in CD8 cells in milk from cows with S. aureus mastitis was found compared with blood in our study, and this finding was consistent with previous findings [26,30] that CD8 cells were the main subpopulation of lymphocytes in quarters from cows inoculated with S. aureus. The extent of CD8 cells in milk was not consistent and varied dependent on the time after infection, and the cells in milk were increased at 9-14 days post-inoculation [27].…”
Section: Discussionsupporting
confidence: 93%
“…This result was similar to the report of Rivas et al [27], who observed increases of CD4 cells in the mammary gland in an experimental study using cows with S. aureus infection. A significant increase in CD8 cells in milk from cows with S. aureus mastitis was found compared with blood in our study, and this finding was consistent with previous findings [26,30] that CD8 cells were the main subpopulation of lymphocytes in quarters from cows inoculated with S. aureus. The extent of CD8 cells in milk was not consistent and varied dependent on the time after infection, and the cells in milk were increased at 9-14 days post-inoculation [27].…”
Section: Discussionsupporting
confidence: 93%
“…These previous studies focused generally on changes of milk composition during the course of an induced mastitis, the time course of effector-cell appearance in the milk, their functional capabilities, and the expression of soluble immune mediators [3,12,41,43].…”
Section: Discussionmentioning
confidence: 99%
“…This may be indicative of the atypical nature of S. aureus Newbould 305 as a representative of S. aureus pathogenic for the udder; further work is therefore needed to fully characterize the Newbould 305 strain. Typically, intramammary S. aureus infections are characterized by high but variable somatic cell counts (11,44), persistence (34,38), variable shedding of bacteria (6,43), and low cure rates (3,9). While S. aureus Newbould 305 is convenient for use in challenge trials, it may not be representative of intramammary S. aureus isolates.…”
Section: Discussionmentioning
confidence: 99%